Conducting transformative research protocols in sports science - Santi, Robin; Isserte, Simon; Gaudin, Cyrille; Chaliès, Sébastien (Frontiers in Sports and Active Living, 2025)
This article presents a methodology for “fundamental field research” in sports science, from a transdisciplinary and transformative perspective. It is based on a close and symmetrical partnership between researchers and practitioners. The approach is structured around four detailed and illustrated methodological stages: (1) researchers develop an auxiliary hypothesis derived from a stabilized theoretical framework; (2) practitioners and researchers co-design an experimental training set-up that puts this hypothesis to the test; (3) this set-up, designed to disrupt ordinary professional practices, is implemented and analyzed; (4) the set-up's spin-offs are identified, both scientifically for the researchers and professionally for the practitioners. This methodology creates a consubstantial relationship between scientific and professional aims, encourages co-production of knowledge, and questions the relationship with sustainability in a field where the demand for immediate performance tends to curb experimental dynamics.